Sete obras brasileiras inéditas para percussão: concepção, colaboração e o processo de criação de solos para instrumentos marginalizados - Silva, Catarina Percinio Moreira da (2014)
This research is organized into two sections: (A) Artistic Production and (B) Article. The first presents the repertoire and program notes, the final recital – held on April 25th, two thousand and fourteen, and the first recital – runs on September 6th, two thousand and Thirteen. The final recital exclusively presents premieres of this research composers, while the qualification recital was developed entirely with the resulting pieces of lifting repertoire for percussion marginalized instruments. Section B presents the paper, which discusses the experience of a collaborative process between performer-composer in the creation of seven new works for solo percussion. Initially, the theoretical apparatus of collaboration is exposed, sectioning the material raised on four types of approach to collaborative relationship. Then we discuss the choice of instruments and the use of marginalized experimental technique to realization of new compositions, expressing an aesthetic preference that agree Cagean thought that all sound is equally valid, and consequently that any object is likely to be the focus of a solo composition. The second part of the article deals with Call for new works for percussion. Initially displays the call on your part, drawn from the understanding gained in the bibliographical survey about collaborative relationship; then explains the process of selection of participants composers and finally lists with data on each of the seven compositions written for this research, using the following instruments: bass drum, tinplate, geophone, gongs Beijing, lion's roar, tambourine and bass drum. As a result of the registration of all the stages of relationship with composers, the third part of the article presents some examples of influences inherent in the collaborative authoring process, and this binding element in the exchange of information between collaborative pair of scores to specific passages. Attachments as well follow the scores of works, the process of collaboration, recorded in detail over the various stages of the proceedings including documents, emails and records exchanged between the performer and composers.